The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1750-3841.15444
|View full text |Cite
|
Sign up to set email alerts
|

Properties of margarines prepared from soybean oil oleogels with mixtures of candelilla wax and beeswax

Abstract: The aim of this study was to examine the physical properties of margarines prepared from oleogels with binary mixtures of candelilla wax (CDW) and beeswax (BW) in soybean oil. Some of the margarines made from oleogels with mixtures of CDW and BW had higher firmness than those made with one wax. For example, a 3% wax margarine made with 25% CDW and 75% BW had significantly higher firmness (0.97 N) than those with 100% CDW (0.59 N) and with 100% BW (0.11 N). Differential scanning calorimetry (DSC) and solid fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 29 publications
(61 reference statements)
4
32
0
Order By: Relevance
“…It has been reported that pristine C31 exhibits three endothermic transitions. These peaks were associated with the transitions of orthorhombic to monoclinic phase, monoclinic to rotator phase, and rotator to liquid phase [ 58 ]. The T m of crude CW was reported as 54.40 °C in the previous work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that pristine C31 exhibits three endothermic transitions. These peaks were associated with the transitions of orthorhombic to monoclinic phase, monoclinic to rotator phase, and rotator to liquid phase [ 58 ]. The T m of crude CW was reported as 54.40 °C in the previous work.…”
Section: Resultsmentioning
confidence: 99%
“…However, the higher T m2 corresponds to hydrocarbons and wax esters of CW, which are mid-melting point compounds [ 40 ]. The T m at ~40 °C is attributed to the monoclinic to the rotator phase transition of hydrocarbon crystals [ 58 ]. On the addition of lecithin, both the melting events, i.e., T m1 and T m2 values, were reduced in all the samples in comparison to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Oleogels are usually produced by dissolving gelators (waxes, fatty acids, fatty alcohols, monoacylglycerols, phytosterols, among others), in low concentration, in vegetable oil, by heating (above the melting point), followed by cooling for gelation (Hwang & Winkler‐Moser, 2020). The replacement of solid fat in W/O emulsion for oleogel is a new approach to these structuring systems (Contreras‐Ramírez et al., 2020).…”
Section: Conventional Crystallization Versus Oleogelationmentioning
confidence: 99%
“…The properties of oleogels often change when they are incorporated into foods, probably due to interactions with other ingredients, such as emulsifiers, preservatives, sugar, water, salt, and processing (Hwang & Winkler‐Moser, 2020). Although the rheological and microstructural properties of oleogels are quite different from those of conventional fats, they yield similar and, frequently, better results when applied in foods (Patel et al., 2020).…”
Section: Oleogel‐based Emulsion Applicationsmentioning
confidence: 99%
See 1 more Smart Citation